Faktor-Faktor Dominan yang Memengaruhi Kualitas Hidup Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisis - Diah Kartika Putri; Salsabila Jelita; Vicko Suswidiantoro; Hardono Hardono (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Patients with Chronic Kidney Disease (CKD) undergoing hemodialysis experience various physical, psychological, and social disturbances that negatively impact their quality of life. While hemodialysis sustains life, this study aimed to identify respondent characteristics and analyze the influence of age, gender, education, occupation, hemodialysis frequency, and duration of hemodialysis on the quality of life of CKD patients undergoing the procedure, as well as to determine the most dominant factor influencing their quality of life. A non-experimental research design with a cross-sectional approach was employed. The study involved 65 respondents selected via purposive sampling and was conducted at the Hemodialysis Unit in February 2026. Data were collected using the KDQOL-SF 36 questionnaire and analyzed using Pearson Correlation, Independent T-test, One-Way ANOVA, and Multiple Linear Regression. Bivariate analysis results indicated that age (p=0,004), occupation (p=0,005), and duration of hemodialysis (p=0,014) were significantly associated with the quality of life of CKD patients, whereas gender (p=0,656) and education level (p=0,117) showed no significant association. Multivariate analysis revealed that the duration of hemodialysis was the most dominant factor influencing patients' quality of life (β=6,781; p=0,028), with the model explaining 25% of the variation in quality of life (R²=0,25). Thus, the duration of hemodialysis is the dominant factor affecting the quality of life of CKD patients; the longer patients undergo hemodialysis therapy, the better their ability to adapt to the disease and treatment, leading to a tendency for improved quality of life.